Development of a prototype voice communication system - Mirza, Farisa Rasinka; Islam, Md. Fakhrul; Ibtida, Anika; Yeasmin, Farha; Shiblee, Shawlee Tasreen (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.